Using ddRADseq to assess the genetic diversity of in-farm and gene bank cacao resources in the Baracoa region, eastern Cuba, for use and conservation purposes - Ramirez-Ramirez, Angel Rafael; Mirzaei, Khaled; Menéndez-Grenot, Miguel; Clapé-Borges, Pablo; Espinosa-Lopéz, Georgina; Bidot-Martínez, Igor; Bertin, Pierre (Frontiers in Plant Science, 2024)
The Baracoa region, eastern Cuba, hosts around 80 % of the country cacao (Theobroma cacao L.) plantations. Cacao plants in farms are diverse in origin and propagation, with grafted and hybrid plants being the more common ones. Less frequent are plants from cuttings, TSH progeny, and traditional Cuban cacao. A national cacao gene bank is also present in Baracoa, with 282 accessions either prospected in Cuba or introduced from other countries. A breeding program associated with the gene bank started in the 1990s based on agro-morphological descriptors. The genetic diversity of cacao resources in Baracoa has been poorly described, except for traditional Cuban cacao, affecting the proper development of the breeding program and the cacao planting policies in the region. To assess the population structure and genetic diversity of cacao resources in Baracoa region, we genotyped plants from both cacao gene bank (CG) and cacao farms (CF) applying a new ddRADseq protocol for cacao. After data processing, two SNPs datasets containing 11,425 and 6,481 high-quality SNPs were generated with 238 CG and 135 CF plants, respectively. SNPs were unevenly distributed along the 10 cacao chromosomes and laid mainly in noncoding regions of the genome. Population structure analysis with these SNP datasets identified seven and four genetic groups in CG and CF samples, respectively. Clustering using UPGMA and principal component analysis mostly agree with population structure results. Amelonado was the predominant cacao ancestry, accounting for 49.22 % (CG) and 57.73 % (CF) of the total. Criollo, Contamana, Iquitos, and Nanay ancestries were detected in both CG and CF samples, while Nacional and Marañon backgrounds were only identified in CG. Genetic differentiation among CG (FST ranging from 0.071 to 0.407) was higher than among CF genetic groups (FST: 0.093–0.282). Genetic diversity parameters showed similar values for CG and CF samples. The CG and CF genetic groups with the lowest genetic diversity parameters had the highest proportion of Amelonado ancestry. These results should contribute to reinforcing the ongoing breeding program and updating the planting policies on cacao farms, with an impact on the social and economic life of the region.